(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Price shows the published or negotiated terms of an exchange transaction for a product, between a producer who aims to achieve a predetermined sales volume and revenue objectives, and prospective customers who seek to maximise their perceptions of value for money in the choices they make between alternative products.